SEMANTIC ANALYSIS OF FIGURATIVE LANGUAGE IN KATY PERRY’S TEENAGE DREAM ALBUM - Nurcahyani, Nova Pinky; Haryanto, Sigit (Universitas Islam Sumatera Utara (UISU), 2025)
This study investigates the semantic construction of figurative language in Teenage Dream, the second studio album by American pop singer Katy Perry. Using a qualitative-descriptive approach, the study draws on Conceptual Metaphor Theory (CMT) and Semantic Field Theory (SFT) to systematically analyze all twelve original songs on the album. The analysis uncovers the strategic use of figurative language especially metaphor, simile, and personification, as a means of encoding complex emotional, psychological, and social meanings. The findings suggest the presence of dominant semantic fields, including love, nostalgia, empowerment, desire, and identity, mapped through embodied imagery such as fire, light, heartbeat, and transformation. These tropes serve not only as poetic embellishments but also as core semantic strategies that construct narrative voice and emotional depth. Furthermore, the study illustrates how figurative language enhances lyrical identity and cultural resonance, particularly in the context of women’s artistic expression in popular music. By highlighting the latent depths in commercially produced lyrics, this study contributes to the broader discourse on the intersection of linguistics, gender, and pop culture. Filling this gap allows for a fuller account of female pop stardom and highlights how Teenage Dream complicates and extends dominant narratives of gender, sexuality, and cultural production in contemporary music studies.